FLUKS GAS METAN (CH4) PADA BUDIDAYA PADI SECARA SYSTEM OF RICE INTENSIFICATION DAN KONVENSIONAL PADA SAWAH PASANG SURUT, LEBAK DAN BERIRIGASI - Zulkarnain Husny (Jurnal Agroekoteknologi, 2010)
ABSTRACT The research was conducted  at fresh water swamp, tidal swamp and irrigated Rice field.Fresh water swamp and Tidal swamp located  countryside Betung, subdistrict Pulau Rimau  and  Sako, subdistrict Rambutan, Regency Musi Banyuasin. While irrigated lowland rice countryside at 0mangunhardjo, Subdistrict Purwodadi, Regency Musi Rawas, from June through October 2010.  The research was aimed to knowing and comprehend or understand  with  to decreased fluxe and emission methane produced and compared with three ecosystem lands  cultivated  S.R.I. The split plot design was appllied in the research. The treatment main plot consisted of  lowland rice  (T) with three factors: fresh water swamp (T1), Tidal swamp (T2) dan Irrigated rice field ( T3) and  sub plot  cultivated  (S) there were two factors: convensional (K) and  S.R.I (S).   The result showed that  the rice cultivated  S.R.I can  decreased of  flux methane  40-71% and  in the form of emission of gas metan one growing season plant may decrease 19-53 %. Being emang three ecosystem may decrease 61-66 %. Measurement of methane gases emission for the three ecosystem rice field to each other every a period of growth showed the declaned at the age 8 week after planting. Later then the total emission of methane increased before harvest.  Key Word:  Convensional, Flux and Emission,  Fresh Water Swamp, Methane, SRI, Tidal swamp.